2017
DOI: 10.1093/cid/cix885
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Human Fecal Carriage of mcr-1–Positive Multidrug-Resistant Enterobacteriaceae Emerge in China in Association With Successful Plasmid Families

Abstract: The high prevalence of mcr-1 in multidrug-resistant E. coli colonizing humans is a clinical threat; diverse genetic mechanisms (strains/plasmids/insertion sequences) have contributed to the dissemination of mcr-1, and will facilitate its persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 50 publications
6
39
3
Order By: Relevance
“…In the present study, 21 colistin resistance mcr-1-carrying E. coli strains were detected from 2632 E. coli (0.80%; 21/2632) isolated from fecal samples, which was close to the 0.1-1% mcr-1 prevalence in Enterobacteriaceae isolates from clinical samples in previous investigations [11][12][13]. Compared with other fecal carriage data, the prevalence of colistin resistance in the present study was lower than that reported in Hongkong (2.08%), Guangzhou (6.2%), and Singapore (8.0%) [14][15][16]. This may be because the stool samples included in our study were obtained only from children.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, 21 colistin resistance mcr-1-carrying E. coli strains were detected from 2632 E. coli (0.80%; 21/2632) isolated from fecal samples, which was close to the 0.1-1% mcr-1 prevalence in Enterobacteriaceae isolates from clinical samples in previous investigations [11][12][13]. Compared with other fecal carriage data, the prevalence of colistin resistance in the present study was lower than that reported in Hongkong (2.08%), Guangzhou (6.2%), and Singapore (8.0%) [14][15][16]. This may be because the stool samples included in our study were obtained only from children.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that mcr-1 is present on many types of plasmids, such as IncI2, IncHI2, IncX4, etc. [14]. These plasmids often carry multiple drug resistance genes, such as β-lactamase gene (bla CTX−M , bla SHV−2 ), bla CMY−2 , etc., fosfomycin resistance gene fosA3, and quinolone resistance gene oqxAB [26,27], and can be transferred to a variety of clinically common host bacteria, such as Pseudomonas aeruginosa, K. pneumoniae, and E. coli, etc., threatening the treatment of drug-resistant gram-negative bacteria [3].…”
Section: Discussionmentioning
confidence: 99%
“…38 In China, several studies focused on the carriage of MCR-producing strains. Zhong et al 39 reported a 6.2% mcr-1 prevalence from inpatients and outpatients of three hospitals, mainly corresponding to MDR E. coli. This prevalence was 1.6% in another study and rose to 9.8% when hospitalized children were targeted.…”
Section: Discussionmentioning
confidence: 98%
“…The broad adaptation of colistin resistance all over the world could be due to the ease with which the mcr-1 gene integrates into various regions (Hadjadj et al, 2017). There is an association with successful plasmid families (Matamoros et al, 2017;Zhong et al, 2018). On the other hand, any association with clonal lineages of E. coli is described .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pap2 gene and ISs IS26 and IS1924 were present in pLREC160_2. Zhong et al (2018) suggested that for IncX4 plasmids IS26/26 structures could be involved in mcr-1 gene mobilization. The BRIG comparison showed that the mcr-1-harboring IncX4 plasmids were genetically homologous between each other as previously described , suggesting that mobilization of the mcr-1 cassette was quite stable within this type of plasmids.…”
Section: Discussionmentioning
confidence: 99%